Effect of Layer Thickness on the Physical and Mechanical Properties of Sand Powder 3D Printing Specimens - Xu, Qing; Jiang, Lishuai; Ma, Changqing; Niu, Qingjia; Wang, Xinzhe (Frontiers in Earth Science, 2021)
The application of sand powder three-dimensional (3D) printing technology in the field of rock mechanics and mining engineering has tremendous potential, but it is still in the preliminary exploration stage. This study investigated the effect of printing layer thickness on the physical and mechanical properties of rock-like specimens with sand powder 3D printing. Quartz sand powder was used as the printing material, and the specimens were prepared with three different layer thicknesses of 0.2, 0.3, and 0.4 mm. Uniaxial compression tests with a combination of digital image correlation (DIC), acoustic emission (AE) and 3D microscope observations were performed to analyze the mechanical properties and failure patterns of the specimens during loading. Experimental findings showed that increasing the layer thickness from 0.2 to 0.4 mm would result in a decrease in the weight, density, uniaxial compression strength, and elastic modulus of the specimens. The stress-strain curve, deformation and failure patterns, crack growth process, and AE characteristics of the specimens with a layer thickness of 0.2 mm are similar to the AE characteristics of rock-like material, whereas the specimens with layer thicknesses of 0.3 and 0.4 mm deform like a ductile material, which is not appropriate for simulation of coal or rock mass. In future studies, rock-like specimens should be prepared with a small layer thickness.